A histopathological snapshot of bladder cancer: a Johannesburg experience of 1480 histopathology reports - Jonosky, Jaclyn; Adam, Ahmed (Springer, 2025)
Purpose: To evaluate the histopathological characteristics of bladder cancer in patients presenting to Johannesburg hospitals over a13-year period (2010–2023). Methods: Following ethical clearance, a retrospective observational, descriptive review of histopathological reports over 13 years was conducted in Johannesburg. Inclusion criteria was bladder biopsies, TURBT specimens, and radical cystectomy (RC) specimens positive for bladder cancer. Exclusion criteria was non-primary bladder cancers (prostate, cervical, colon) and urothelial carcinoma of upper tract origin (N=970). Of the initial specimens N=2450), 1480 met the inclusion criteria, representing 858 patients, owing to multiple transurethral resections of bladder tumours (TURBT). Categorical variables were summarised as counts and percentages, while numerical variables were reported as means with standard deviations or medians with interquartile ranges, depending on data distribution and tested via the Shapiro‒Wilk test. Statistical comparisons were performed using Fisher’s exact test (sex), one-way ANOVA, or the Kruskal‒Wallis test (age). Statistical signifi cance was set at p<0.05. Results: Urothelial carcinoma accounted for 88.8% of bladder cancer, squamous cell carcinoma (7.7%), adenocarcinoma (1.5%), and other malignancies (2%). High-grade urothelial carcinoma was predominant at 75%. Non-muscle invasive disease accounted for 72% of these cases, while 28% were muscle invasive. Data from radical cystectomies showed a high proportion of aggressive and advanced disease. Conclusions: The study highlights the predominance of high-grade non-muscle invasive bladder cancer in Johannesburg, consistent with global trends. The findings suggest a shift in bladder cancer trends in Johannesburg away from assumed squamous cell carcinoma towards urothelial carcinoma.
Keywords: Bladder cancer; Urothelial carcinoma; Histopathology; Johannesburg; Squamous cell carcinoma; Non-muscle invasive bladder cancer; Muscle-invasive bladder cancer; SDG-3: Good health and well-being